Systematicity in language use of the L2 learners of English: A corpus-based study of the students’ written production - Adamova, K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2025)
The current study scrutinizes one of the most complex skills to develop in the second language learning process — writing. It aims to explore major trends in the complexity of L2 writing to depict written language production. The corpus of the study is built from the exam papers at the written text production part of the Basic English Language examination (BLE). BLE is the obligatory examination that needs to be passed by English majors at the Hungarian University and plays a crucial role in the educational field. L2 English learners tend to produce a text and prove B2+ level proficiency according to Common European Framework of Reference (CEFR). The research method includes manual analysis based on six categories of grammatical features (incl. Verb agreement; Prepositions; Article Use; Capitalization; Word order; and Spelling). The analysis could help reveal the systematicity in their performance that L2 learners tend to have in their writing based on the corpus in the selected corpus. Among the most common ones are prepositions, more precisely their omission and misuse, verb agreement, and spelling. To identify the nature of the errors, a deep and thorough analysis should be conducted. The present piloting study provides significant insights, and its outcomes are crucial for further research design of the analysis of L2 writing.
Ағылшын тілін екінші тіл ретінде үйренушілердің тілдік қолдану жүйелілігі: Студенттердің жазбаша жұмыстарына корпусқа негізделген зерттеу
Систематичность в письменном продуцировании речи изучающих английский язык как второй: корпусное исследование письменных текстов студентов
Keywords: language learning; written text production; grammatical analysis; world English; learners